The effect of different neutral-detergent-soluble polysaccharides in digestive cynetics in vitro of neutral detergent forrage fiber and the synthesis of microbial protein - Rosendo, Oswaldo; Beth Hall, Mary; Staples, Charles; Bates, Douglas (Revista Científica de la Facultad de Ciencias Veterinarias)
The purposes of this experiment were to compare the pH-independent effects of starch, fructans, and pectins, described in this study as neutral detergent-soluble polysaccharides (NDSP), on forage neutral detergent fiber (NDF) digestion kinetics and microbial protein synthesis using the in vitro ruminant digestion technique. Isolated NDF from alfalfa (A), Bermuda grass (B), and timothy (T) was fermented alone (C) or with dahlia tuber inulin (I), citrus pectin (P), or corn starch (S) as NDSP sources. In blended samples, the NDF:NDSP ratio was 60:40. Individual forages (A, B or T) were fermented in separate duplicate runs using 0, 2, 4, 6, 12, 18, 24, 30, 36, 48, 72, and 96 h time points. Trichloroacetic acid was used to precipitate microbial and substrate crude protein in triplicate treatments and blanks at 0 and 24 h. The 24 h treatment values corrected for blank and 0 h treatment means estimated microbial crude protein yield (TCAP) at 24 h. Kinetics of NDF digestion were calculated by fitting the NDF disappearance data to the Mertens model. Both fermentation lag time (h) and the fractional rate of digestion (Kd; h-1) were calculated iteratively by NLIN”™s Marquardt procedure of SAS. Results are listed in treatment order C, I, P, and S. The NDF kd values were 0.084, 0.099, 0.049, and 0.139 for A, 0.040, 0.035, 0.026, and 0.062 for B, and 0.069, 0.077, 0.069, and 0.088 for T. Lag time (hours) values were A: 6.73, 7.72, 0.07, and 8.03; B: 7.02, 7.64, 8.86, and 10.27; and T: 6.80, 6.41, 3.71, and 7.23. The DTCAP values (mg of CP/g of substrate OM) were A: 32.86, 75.95, 50.62, and 59.29; B: 29.26, 53.75, 24.70, and 51.24; and T: 40.48, 79.77, 51.30, and 68.81. Neither the lag time nor Kd were affected by NDSP addition to forage NDF (P>0.05). The DTCAP of forage incubated with P was always less than that incubated with I and S, and the effect of both I and S were similar except for Alfalfa NDF. The neutral detergent-soluble polysaccharides did not affect kinetics of forage NDF digestion when pH of cultures was maintained over 6.6 but, they differed in their effects on microbial protein production in vitro. Overall, treatment I and S favored greater in vitro microbial protein production than P.